2002
DOI: 10.1073/pnas.162366299
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 is required for vascular development and is a mediator of VEGF-dependent angiogenesis in zebrafish

Abstract: Neuropilin-1 (NRP1) is a cell-surface receptor for both vascular endothelial growth factor 165 (VEGF165) and class 3 semaphorins that is expressed by neurons and endothelial cells. NRP1 is required for normal developmental angiogenesis in mice. The zebrafish is an excellent system for analyzing vascular development. Zebrafish intersegmental vessels correspond to mammalian capillary sprouts, whereas the axial vessels correspond to larger blood vessels, such as arteries. The zebrafish NRP1 gene (znrp1) was isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
147
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(158 citation statements)
references
References 27 publications
11
147
0
Order By: Relevance
“…In addition to its role as a Sema3A receptor, neuropilin-1 is a co-receptor for a specific isoform of VEGF165 and guides endothelial cell migration during vascular morphogenesis (Soker et al, 1998;Lee et al, 2002). The role of neuropilin-1 in tumors has been mostly studied in the context of its interaction with VEGF165 and related to tumor angiogenesis and tumor cell survival (Miao et al, 2000;Bachelder et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role as a Sema3A receptor, neuropilin-1 is a co-receptor for a specific isoform of VEGF165 and guides endothelial cell migration during vascular morphogenesis (Soker et al, 1998;Lee et al, 2002). The role of neuropilin-1 in tumors has been mostly studied in the context of its interaction with VEGF165 and related to tumor angiogenesis and tumor cell survival (Miao et al, 2000;Bachelder et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…deficient mouse and zebrafish models established an essential role of NRP1 in the development of the embryonic nervous and cardiovascular systems. [20][21][22][23] NRPs are also highly expressed in diverse tumor cell lines and human neoplasms and have been implicated in tumor growth and vascularization. [2][3][4]24,25 More recently, it has been reported that NRP1 might have a role as a novel mediator of the primary immune response, as well as in tissue regeneration and repair.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The cells (passages [20][21][22][23][24][25][26][27][28][29][30] were grown at 371C in a humidified 5% CO 2 atmosphere, and split at a 1:10 ratio, once a week. After growth to a subconfluent state, cells were washed once, made quiescent by incubation in serum-and supplementfree medium for 48 h, and then used for experiments.…”
Section: Cell Culturementioning
confidence: 99%
“…The tyrosine kinase domain between human and zebrafish VEGF-R2/KDR is highly conserved (Habeck et al, 2002). In addition, PTK 787 has been shown to block vascular development in zebrafish embryos (Chan et al, 2002;Lee et al, 2002) and VEGF-induced autophoshorylation of zebrafish VEGF-R2/flk-1 (Chan et al, 2002). Hence, we used PTK 787, and additionally AAC 789, to test our hypothesis that signaling through VEGF-Rs is required for valve development.…”
Section: Ptk 787 and Aac 789 Inhibit Vegf-induced Nuclear Localizatiomentioning
confidence: 99%
“…Circulation through the heart was visualized by injecting FITC-dextran (Sigma) into the sinus venosa as described (Lee et al, 2002). Untreated and AAC 789-treated embryos were injected approximately 50 -56 hpf and visualized by fluorescence microscopy within 30 min of the injection.…”
Section: Micro-angiography Of Zebrafish Embryosmentioning
confidence: 99%